2019
DOI: 10.1590/1519-6984.188129
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synadenium grantii latex proteases in nematicidal activity on Meloidogyne incognita and Panagrellus redivivus

Abstract: Synadenium grantii is a Euphorbiaceae plant commonly found in Brazil, known as Janaúba or Leitosinha, whose latex is traditionally used for several purposes. However, it is not known whether the nematicidal action of this plant latex occurs due to the action of proteases. The present work aims to evaluate the nematicidal activity of proteases from Synadenium grantii latex on Meloidogyne incognita and Panagrellus redivivus. S. grantii latex used in the present study was collected from specimens found in Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The efficiency of E. trigona crude extract in nematodes reduction is showed by the high reduction percentage observed, with 96% reduction in 24 hours of treatment, when compared to control (Figure 3). In a similar study, the proteases from Synadenium grantii reduced the number of M. incognita juveniles in 100% after 24 hours of treatment (Gomes et al, 2019). The present study is the first report of E. trigona latex with nematicidal activity, therefore more studies regarding latex proteases action on nematodes are needed.…”
Section: Resultsmentioning
confidence: 53%
“…The efficiency of E. trigona crude extract in nematodes reduction is showed by the high reduction percentage observed, with 96% reduction in 24 hours of treatment, when compared to control (Figure 3). In a similar study, the proteases from Synadenium grantii reduced the number of M. incognita juveniles in 100% after 24 hours of treatment (Gomes et al, 2019). The present study is the first report of E. trigona latex with nematicidal activity, therefore more studies regarding latex proteases action on nematodes are needed.…”
Section: Resultsmentioning
confidence: 53%
“…These free-living nematodes are excellent models as they are similar to parasitic species (Srinivasan et al, 2013;Burns et al 2015). In previous studies, nematodes of the genus Panagrellus were successfully used as a model for evaluating nematicidal activity (Soares et al, 2015;Gomes et al, 2018;Ferreira et al, 2019). Thus, a significant nematicidal activity against these organisms points to a great potential for use on Research, Society andDevelopment, v. 12, n. 4, e15712440989, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i4.40989 parasitic nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…population in the soil is protease. Protease enzyme was reported to be capable of degrading root-knot nematode cuticle and eggs that are composed of proteins (De Souza Gouveia et al 2017;Gomes et al 2019). Safni et al (2018) reported that bacteria with the capability of producing chitinase and protease enzymes could in vitro lyse Meloidogyne spp.…”
Section: Discussionmentioning
confidence: 99%